Efficient Delivery of Transducing Polymer Nanoparticles for Gene-Mediated Induction of Osteogenesis for Bone Regeneration - Jalal, Aveen R.; Dixon, James E. (Frontiers in Bioengineering and Biotechnology, 2020)
Developing non-viral gene therapy vectors that both protect and functionally deliver nucleic acid cargoes will be vital if gene augmentation and editing strategies are to be effectively combined with advanced regenerative medicine approaches. Currently such methodologies utilize high concentrations of recombinant growth factors, which result in toxicity and off-target effects. Herein we demonstrate the use of modified cell penetrating peptides (CPPs), termed Glycosaminoglycan (GAG)-binding Enhanced Transduction (GET) peptides with plasmid DNA (pDNA) encapsulated poly (lactic-co-glycolic acid) PLGA nanoparticles (pDNA-encapsulated PLGA NPs). In order to encapsulate the pDNA, it was first condensed with a cationic low molecular weight Poly L-Lysine (PLL) into 10-50nm NPs followed by encapsulation in PLGA NPs by double emulsion; yielding encapsulation efficiencies (EE) of 30%. PLGA NPs complexed with GET peptides show enhanced intracellular delivery (up to seven fold) and transfection efficiencies (up to five orders of magnitude). Moreover, the pDNA cargo has enhanced protection from nucleases (such as DNase I) promoting their translatability. As an example, we show these NPs efficiently deliver pBMP2 which can promote bone differentiation in vitro. Gene delivery to human mesenchymal stem cells (hMSCs) inducing their osteogenic programming was confirmed by Alizarin red calcium staining and bone lineage specific gene expression (Q RT-PCR). By combining simplistic and FDA-approved PLGA polymer nanotechnology with the GET delivery system, therapeutic non-viral vectors could have significant impact in future cellular therapy and regenerative medicine applications.